Casting the George Floyd story in a broader context - Gerson Uaripi Tjihenuna (The Thinker)
On 9 June 2020, viewers around the globe were glued to international TV networks to watch the live coverage of the funeral of George Floyd, an African-American man who was killed by the police during an arrest in Minneapolis on May 25 2020. Police brutality against African-Americans is not something new and this is what led to the slogan ‘Black Lives Matter’ that has been the lodestar of the recent waves of protest. The American Police Force is embedded with systemic racism which seems to have been reinforced by Donald Trump’s presidency.